Nyctanthes arbor-tristis attenuates hyperglycemia: an integrated experimental and computational investigation - Brij Raj Singh; Jagat Pal Yadav; Ashish R. Dwivedi; Ankit Kumar Singh; Vikas Kumar; Habibullah Khalilullah; Prateek Pathak; Amita Verma (DARU Journal of Pharmaceutical Sciences, 2026)

Development of biomimetic mouldable osseous scaffold engineered from bioactive decellularized extracellular matrix-polymer-gel composite: a potential bone substitute - Prarthana R; Rekha Pathak; Deepak Kumar; Vinodhkumar Obli Rajendran; KS Kamalesh; T. Saikumar; Bhanu Pratap Singh; Rohit Kumar (Cell and Tissue Banking, 2026)

Integrated pond co-culture of Penaeus vannamei with red seaweeds: Implications for nutrient uptake and dual production performance - K. Surya; Madhuri Pathak; Munilkumar Sukham; Thongam Ibemcha Chanu; Layana Porayil; Vaibhav A. Mantri; Debajit Sarma; G. Harini; P.S. Prathib; Bhavik Kantilal Bhagiya; Komal R. Chilveri (Algal Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Early-Middle Pleistocene to recent paleoceanographic variability in the Agulhas system (southwestern Indian Ocean) induced by fluctuations in the Antarctic Circumpolar Current - A.V. Del Gaudio; V.P. Singh; A. Arrigoni; X. Puentes-Jorge; R. Dwivedi; S. Pathak; A.R. Lam (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

Influence of Soil Carbon Pools and Indices on Zinc Sorption Mechanisms and Distribution in Diverse Potato-based Cropping Systems of the Western Indo-Gangetic Plains - Shivam Singh; Debashis Dutta; Satendra Kumar; Jagannath Pathak; Uday Pratap Shahi; B. P. Dhyani; Ankit Tiwari; Mahendra Pratap Singh; R. B. Verma; Richa Raghuvanshi (Potato Research, 2026)

Adverse childhood experiences, adult adiposity, and risk of young-onset breast cancer subtypes in a population-based case-control study - Lydia Marcus Post; Young Ik Cho; James Topitzes; DPhuong Do; Dorothy R. Pathak; Ann S. Hamilton; Amani M. Nuru-Jeter; Kelly A. Hirko; Jamila L. Kwarteng; Richard Houang; Ann G. Schwartz; Ellen M. Velie (Cancer Causes & Control, 2026)
Purpose Adverse childhood experiences (ACEs) are hypothesized to increase breast cancer risk via social and physiological pathways, yet associations between ACEs and young-onset breast cancer (BC) subtypes–and potential mediators (e.g., adiposity) of these associations–are largely unstudied. We sought to evaluate associations between ACEs and young-onset BC molecular subtypes, and the potential mediating effects of adiposity, in a population-based case–control study of invasive young-onset BC. Methods Cases (n = 1,754) were identified from the Los Angeles County and Metropolitan Detroit SEER registries, 2010–2015, and area-based, frequency-matched controls (n = 1,350) sampled from the 2010 Census. Associations between ACEs aged < 18 years and young-onset BC (diagnosed ages 20 to < 50 years), overall and by subtype (luminal A, luminal B, HER2 + , triple negative [TN]), were examined using weighted logistic regression. Adult adiposity (i.e., body mass index 12 months before diagnosis, waist circumference at interview) was evaluated as a mediator of these associations using weighted path analyses. Results ACEs (≥ 1 vs 0) were not significantly associated with young-onset BC (all p trend > 0.10); however, reporting one ACE (vs 0) was associated with TN (odds ratio [OR] = 1.85 [95% confidence interval [95%CI] = 1.08–3.16]). For individual ACEs, death of a loved one (vs 0 ACEs) was associated with HER2 + (OR = 2.50 [95%CI = 1.06–5.88]) and potentially TN (OR = 1.72 [95%CI = 0.96–3.10]) young-onset BC; other associations were non-significant. In path analyses, ACEs had a significant total effect on luminal A (β = 0.08, p = 0.03) and TN (β = 0.13, p < 0.01) tumors, with adiposity mitigating this association for luminal A tumors (β = -0.01, p = 0.04; TN β = 0.00, p > 0.05). Conclusions Bereavement during childhood was associated with higher odds of HER2 + young-onset BC, and there was some evidence of an association between ACEs and other young-onset BC subtypes, particularly TN.

Estimating carbon sequestration in orchards of semi-arid tropics: A modeling approach - R Siddesh; H. Pathak; S.B. Chavan; V.D. Kakade; S.S. Salunkhe; A.R. Uthappa; N. Paul; H.M. Halli; K.S. Reddy (Biomass and Bioenergy, 2026)

Understanding conservation priorities for Dactylorhiza hatagirea (D.Don) Soo from the Northwestern Himalayas through analysis of morphometrics and population genetics - Pratibha Jaryal; Promila Pathak; Ashish R. Warghat (Plant Systematics and Evolution, 2026)

Interfacial-bulk electrochemistry of sodium-ion storage in multiwalled carbon nanofiber anode with incorporated Mn−N4 single-atoms - Anubha Yadav; Prakash Kumar Pathak; Babasaheb M. Matsagar; Rahul Patil; Norman C.-R. Chen; Rajashri R. Urkude; Masaki Ujihara; Kevin C.-W. Wu; Rahul R. Salunkhe; Saikat Dutta (Chemical Engineering Journal, 2025)

A data-driven ground motion model of energy spectrum in the Indo-Burma region using artificial neural networks - Ajay Kumar Pathak; S. T. G. Raghukanth; C. V. R. Murty (Bulletin of Earthquake Engineering, 2025)

Identification of an endangered and medicinally important Himalayan orchid, Dactylorhiza hatagirea D.Don Soo using DNA barcodes and development of an efficient in vitro propagation protocol utilizing embryo culture technique - Pratibha Jaryal; Promila Pathak; Vandana Jaiswal; Ashish R. Warghat (In Vitro Cellular & Developmental Biology - Plant, 2025)

Climate Resilient Crop Varieties: Mainstreaming to Improve Yield and Moderate Farmers’ Risk - D. K. Yadava; Ranjay K. Singh; V. B. Patel; T. R. Sharma; S. K. Singh; Sudhakar Pandey; P. R. Choudhury; Firoz Hossain; R. R. Burman; U. S. Gautam; Himanshu Pathak (Anthropocene Science, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Steroidal glycoside-rich extract of fenugreek seeds mitigates obesity-induced insulin resistance via attenuation of low-grade inflammation - Sumati Sen; Ashutosh K. Tiwari; Monika Binwal; Monazza Israr; Anant Kumar; Nandini Pathak; Kaveri R. Washimkar; CH Ratnasekhar; Madhav Nilakanth Mugale; Arvind S. Negi; Dnyaneshwar U. Bawankule (Food Research International, 2025)

Development of different regenerative modes for efficient propagation and phytochemical analysis in Tylophora indica (Burm. F.) Merrill: an important medicinal plant - Swati R. Patel; Ashutosh Pathak; Aruna Joshi; Neeta Shrivastava; Sonal Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Fruit tree-based restoration strategy to mitigate greenhouse gas emissions, and enhance the profitability of degraded land in semi-arid tropics - R. Siddesh; Himanshu Pathak; S.B. Chavan; Hanamant M. Halli; V.D. Kakade; A.S. Morade; Sanjni Salunkhe; D.D. Nangare; V.N. Salunkhe; A.K. Singh; Aliza Pradhan; K. Sammi Reddy (Science of The Total Environment, 2025)

Detection of elevated CO₂ and CH₄ emissions from power plant and landfill sites using airborne and spaceborne imaging spectroscopy - Hasmukh K. Varchand; Mehul R. Pandya; Jalpesh A. Dave; Parthkumar N. Parmar; Dhruv D. Desai; Manoj Singh; Dhiraj B. Shah; Vishal N. Pathak; Himanshu J. Trivedi (Atmospheric Pollution Research, 2025)

Design and Validation of a Low-Cost, Portable Arduino-Based Platform for Assessing Physicochemical Drinking Water Quality Across Urban and Peri-urban Areas of Delhi and Surrounding Regions - Arjun Singh; Rahul Arya; Nikki Choudhary; Navraj Poudel; Poonam Arora; K. K. Maurya; T. K. Mandal; S. K. Sharma; Prashant Kumar; Saurabh Pathak; R. P. Pant (Water Conservation Science and Engineering, 2025)

Impact of abiotic factors on different developmental stages of Antheraea proylei (Lepidoptera: Saturniidae) reared on Quercus floribunda and Q. glauca - Gunjan Pathak; Himanshu Pande Lohani; Jeetika Siddhu; B. R. Kaushal; A. S. Verma (International Journal of Tropical Insect Science, 2025)

Appraisal on Energy Coefficients in Energetic Analysis of Agricultural Production System and Energetic Assessment on Sugarcane production - P. Subramanian; R. Mahendiran; B. Prabha; Gitanjali Jothiprakash; Ramesh Desikan; Bhargav Vinod Kumar; K. C. Pandey; Bhim Sen Pathak (Sugar Tech, 2025)

Pomegranate as a natural remedy for gastric ulcers prevention: a review of its gastroprotective mechanisms and pharmacological benefits - Mohammad Yasin Zamanian; Zhanna R. Gardanova; Ahmed Hjazi; Subasini Uthirapathy; S. Renuka Jyothi; Debasish Shit; Piyus Kumar Pathak; Suman Saini; Ahmad Jahdari; Maryam Golmohammadi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Combined Genome-Wide Association Study and Expression Analysis Unravels Candidate Genes Associated with Seed Weight in Moth Bean [Vigna aconitifolia (Jacq.) Marechal] - Arvind Kumar Yadav; Chandan Kumar Singh; Dhammaprakash P. Wankhede; Rajwant K. Kalia; Seema Pradhan; Shraddha Ujjainwal; Tanmaya Kumar Sahu; N. S. Nathawat; R. K. Kakani; Reena Rani; Rajesh Kumar; Rakesh Pathak; et al. (Journal of Plant Growth Regulation, 2025)

Integrating socio-economic variables in urban flood damage assessments: a case study of Bengaluru, India - Abhishek A. Pathak; Apoorva R. Mathad; Alexandre S. Gagnon (Natural Hazards, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

DNA barcoding of Spiraea hypericifolia L. and development of an efficient micropropagation using nodal explant: an economically important ornamental and medicinal shrub of Eurasian areal - Vitaliy Kirillov; Ashutosh Pathak; Swati R. Patel; Meirzhan Daulenova; Damira Dyussembekova; Tamara Stikhareva; Ardak Sapiyeva; Aidana Nurtaza; Zhanargul Zhanybekova; Almagul Kakimzhanova (In Vitro Cellular & Developmental Biology - Plant, 2025)

An efficient clonal propagation of a medicinally important and endangered Himalayan herb, Dactylorhiza hatagirea D.Don Soo using shoot meristem culture and genetic fidelity analysis - Pratibha Jaryal; Promila Pathak; Ashish R. Warghat (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A hybrid physics-based method for estimating land surface temperature using radiative transfer simulations and machine learning model from Sentinel-3A SLSTR observations - Jalpesh A. Dave; Vedant Pandya; Frank-M. Goettsche; Hasmukh K. Varchand; Parthkumar N. Parmar; Dhruv D. Desai; Disha B. Kardani; Dhiraj B. Shah; Ashwin Gujrati; Vishal N. Pathak; Himanshu J. Trivedi; Mehul R. Pandya (Earth Science Informatics, 2025)

Emergence of Aeromonas salmonicida subsp. masoucida MHJM250: unveiling pathological characteristics and antimicrobial susceptibility in golden mahseer, Tor putitora (Hamilton, 1822) in India - Krishna Kala; Sumanta Kumar Mallik; Neetu Shahi; Richa Pathak; Prerna Sharma; Suresh Chandra; R. S. Patiyal; Veena Pande; Nityanand Pandey; Amit Pande; Pramod Kumar Pandey (Veterinary Research Communications, 2024)

Development of a High-Fidelity Benchtop Model for Simultaneous Flow, Pressure, and Imaging Assessment of Transarterial Embolization Procedures - Prateek C. Gowda; Robert M. Weinstein; Akanksha Bhargava; Janaka Senarathna; Ryan Q. Stewart; Pallavi V. Ekbote; Mantej Singh; Emily Guan; Serena Banghar; Arvind P. Pathak; Clifford R. Weiss (Cardiovascular Engineering and Technology, 2024)

Ultrasonic Assisted Synthesis of CuFe2O4-Ag infused Gum Hydrogels Nanocomposite for photocatalytic Degradation of Organic Dye from Wastewater - Meenu; Pratibha Sharma; Roli Purwar; Navita Sharma; Pooja Rawat; Seema R. Pathak; Atul Thakur; Hyunook Kim; Monu Verma; Sudip Majumder; Chandra Mohan Srivastava (Water, Air, & Soil Pollution, 2024)

Screening of Potato Varieties for Resistance to Potato Tuber Moth, Phthorimaea operculella (Zeller) in Meghalaya, India - Primiya R. Lyngkhoi; Kennedy Ningthoujam; Mahesh Pathak; Ngursangzuala Sailo (Potato Research, 2024)

Morpho-cultural and molecular variability in Rhizoctonia solani isolates from rice-vegetable cropping alluvial zone of West Bengal - Krishna Ray; Sujit Kumar Ray; Subrata Dutta; Ashis Roy Barman; Shikha Pathak; Tasvina R. Borah (Indian Phytopathology, 2024)

Adoption of Trench Method Cane Planting and its Role in Increasing Cane Yield and Sugar Recovery in Uttar Pradesh - S. K. Pathak; R. A. Kushwaha; A. K. Sah (Sugar Tech, 2024)

Lifetime alcohol consumption patterns and young-onset breast cancer by subtype among Non-Hispanic Black and White women in the Young Women’s Health History Study - Kelly A. Hirko; Darek R. Lucas; Dorothy R. Pathak; Ann S. Hamilton; Lydia M. Post; Ugonna Ihenacho; Nicole Bohme Carnegie; Richard T. Houang; Kendra Schwartz; Ellen M. Velie (Cancer Causes & Control, 2024)

An efficient micropropagation protocol for an endangered tree species Aflatunia ulmifolia (Franch.) Vassilcz - Vitaliy Kirillov; Ashutosh Pathak; Swati R. Patel; Mariya Serafimovich; Meirzhan Daulenova; Mikhail Gorbachenkov; Mussa Zholdasbayev; Tamara Stikhareva (In Vitro Cellular & Developmental Biology - Plant, 2024)

CO2 concentration retrieval and emission rate estimation over Indian thermal power plants using radiative transfer approach and AVIRIS-NG data - Hasmukh K. Varchand; Mehul R. Pandya; Jalpesh A. Dave; Parthkumar N. Parmar; Himanshu J. Trivedi; Dhiraj B. Shah; Vishal N. Pathak (Remote Sensing Applications: Society and Environment, 2024)

Comparative evaluation of native top feeds of western Himalayas for utilization as goat’s ration in mash and block form - Imran Ahmad Ganai; R. K. Sharma; Ankur Rastogi; A. K. Pathak; Vijay Kumar Sharma (Tropical Animal Health and Production, 2023)

A search for potential anti-HIV phytoconstituents from the natural product repository - Dharmraj V. Pathak; Sneha R. Sagar; Hardik G. Bhatt; Paresh K. Patel (Advances in Traditional Medicine, 2023)

Exosomes from metastatic colon cancer cells drive the proliferation and migration of primary colon cancer through increased expression of cancer stem cell markers CD133 and DCLK1 - K. Yasodha; L. Lizha Mary; Pathak Surajit; R. Satish (Tissue and Cell, 2023)

Quantification of Cerebral Vascular Autoregulation Immediately Following Resuscitation from Cardiac Arrest - Yucheng Shen; Qihong Wang; Hiren R. Modi; Arvind P. Pathak; Romergryko G. Geocadin; Nitish V. Thakor; Janaka Senarathna (Annals of Biomedical Engineering, 2023)

Correction to: Algorithm for the Estimation of Continental Scale Land-Surface Broadband Albedo from INSAT-3D Imager Data - Mehul R. Pandya; Vishal Pathak; Nitesh Kaushik; Himanshu J. Trivedi (Journal of the Indian Society of Remote Sensing, 2023)

Elicitor mediated enhancement of shoot biomass and lupeol production in Hemidesmus indicus (L.) R. Br. ex. Schult. and Tylophora indica (Burm. F.) Merrill using yeast extract and salicylic acid - Ashutosh R. Pathak; Swati R. Patel; Aruna G. Joshi; Neeta Shrivastava; Gaurang Sindhav; Sonal Sharma; Hafsa Ansari (Natural Product Research, 2023)

Phylogenetic distribution, structural analysis and interaction of nucleotide excision repair proteins in cyanobacteria - Prashant R. Singh; Amit Gupta; Rajneesh; Jainendra Pathak; Rajeshwar P. Sinha (DNA Repair, 2023)

Enhancing Crop Productivity and Profitability of Autumn Sugarcane with Intercropping of Winter Vegetables in Real Farming Situations of North-Central India - S. N. Singh; Chandra Gupta; V. K. Singh; A. D. Pathak; A. K. Sah; M. K. Tripathi; Sanjiv Gupta; J. R. Patnaik (Sugar Tech, 2023)

Water trading as a tool to combat economic losses in agriculture under climate change - Xiaoliang Han; Proloy Deb; Nicholas R. Magliocca; Denis Nadolnyak; Hamed Moftakhari; Ruchie Pathak; Hamid Moradkhani (Sustainability Science, 2023)

Water and wastewater quality prediction: current trends and challenges in the implementation of artificial neural network - Anuja R. Jadhav; Pranav D. Pathak; Roshani Y. Raut (Environmental Monitoring and Assessment, 2023)

Micropropagation of Cotoneaster melanocarpus Fisch. ex A.Blytt: an economically important ornamental plant - Vitaliy Kirillov; Ashutosh Pathak; Swati R. Patel; Meirzhan Daulenova; Damira Dyussembekova; Tamara Stikhareva; Alimzhan Rakhimzhanov; Almagul Kakimzhanova (In Vitro Cellular & Developmental Biology - Plant, 2023)

Integrated Approaches to Develop Drought-Tolerant Rice: Demand of Era for Global Food Security - Arun Kumar; R. S. Sengar; Rajesh Kumar Pathak; Amit Kumar Singh (Journal of Plant Growth Regulation, 2023)

Recycling of platinum group metals from exhausted petroleum and automobile catalysts using bioleaching approach: a critical review on potential, challenges, and outlook - Ashish Pathak; Hanadi Al-Sheeha; R. Navvamani; Richa Kothari; Meena Marafi; Mohan S. Rana (Reviews in Environmental Science and Bio/Technology, 2022)

Relevance of phosphate solubilizing microbes in sustainable crop production: a review - F. Fatima; M. M. Ahmad; S. R. Verma; N. Pathak (International Journal of Environmental Science and Technology, 2022)

Relic surface water (clay-pore water) input triggers arsenic release into the shallow groundwater of Bengal aquifers - Pousali Pathak; Prosenjit Ghosh; Sanchita Banerjee; R S Chatterjee; Noor Muzakkira; Pradip K Sikdar; Utsab Ghosal; Mao-Chang Liang; Kathiravan Meeran (Journal of Earth System Science, 2022)

Prolonged effects of DPP-4 inhibitors on steato-hepatitic changes in Sprague–Dawley rats fed a high-cholesterol diet - Rashmi Pathak; Avinash Kumar; Henry A. Palfrey; Kirsten P. Stone; Narayan R. Raju; Thomas W. Gettys; Subramanyam N. Murthy (Inflammation Research, 2022)

Climate risk insurance in Pacific Small Island Developing States: possibilities, challenges and vulnerabilities—a comprehensive review - Devendra Kumar Jain; Asif Chida; R. D. Pathak; Raghbendra Jha; Stephanie Russell (Mitigation and Adaptation Strategies for Global Change, 2022)

A review on interplay between small RNAs and oxidative stress in cancer progression - Aparimita Das; Harsha Ganesan; Sushmitha Sriramulu; Francesco Marotta; N. R. Rajesh Kanna; Antara Banerjee; Fang He; Asim K. Duttaroy; Surajit Pathak (Molecular and Cellular Biochemistry, 2021)

Theory, methods, and operational results of the Young Women’s Health History Study: a study of young-onset breast cancer incidence in Black and White women - Ellen M. Velie; Lydia R. Marcus; Dorothy R. Pathak; Ann S. Hamilton; Ralph DiGaetano; Ron Klinger; Bibi Gollapudi; Richard Houang; Nicole Carnegie; L. Karl Olson; Amani Allen; Zhenzhen Zhang; et al. (Cancer Causes & Control, 2021)
Purpose The etiology of young-onset breast cancer (BC) is poorly understood, despite its greater likelihood of being hormone receptor-negative with a worse prognosis and persistent racial and socioeconomic inequities. We conducted a population-based case–control study of BC among young Black and White women and here discuss the theory that informed our study, exposures collected, study methods, and operational results. Methods Cases were non-Hispanic Black (NHB) and White (NHW) women age 20–49 years with invasive BC in metropolitan Detroit and Los Angeles County SEER registries 2010–2015. Controls were identified through area-based sampling from the U.S. census and frequency matched to cases on study site, race, and age. An eco-social theory of health informed life-course exposures collected from in-person interviews, including socioeconomic, reproductive, and energy balance factors. Measured anthropometry, blood (or saliva), and among cases SEER tumor characteristics and tumor tissue (from a subset of cases) were also collected. Results Of 5,309 identified potentially eligible cases, 2,720 sampled participants were screened and 1,812 completed interviews (682 NHB, 1140 NHW; response rate (RR): 60%). Of 24,612 sampled control households 18,612 were rostered, 2,716 participants were sampled and screened, and 1,381 completed interviews (665 NHB, 716 NHW; RR: 53%). Ninety-nine% of participants completed the main interview, 82% provided blood or saliva (75% blood only), and SEER tumor characteristics (including ER, PR and HER2 status) were obtained from 96% of cases. Conclusions Results from the successfully established YWHHS should expand our understanding of young-onset BC etiology overall and by tumor type and identify sources of racial and socioeconomic inequities in BC.

Spent marigold flower meal as an alternate feed for goats - Gagandeep Kour; R. K. Sharma; Nazam Khan; A. K. Pathak; Ankur Rastogi; Vijay Kumar Sharma (Tropical Animal Health and Production, 2021)

Algorithm for the Estimation of Continental Scale Land-Surface Broadband Albedo from INSAT-3D Imager Data - Mehul R. Pandya; Vishal Pathak; Nitesh Kaushik; Himanshu J. Trivedi (Journal of the Indian Society of Remote Sensing, 2021)

Variation in the Nutritional Composition of Soft and Hard Blue Swimming Crabs ( Portunus pelagicus ) Having Good Export Potential - Neeraj Pathak; Robinson Jeya Shakila; Geevaretnam Jeyasekaran; Padmavathy P; Neethiselvan N; R. Shalini; Ulaganathan Arisekar; Akalesh Patel; Udhaya Kumar; Asha Hema Malini; R Mayilvahnan (Journal of Aquatic Food Product Technology, 2021)

DNA interaction, in vivo and in vitro cytotoxicity, reactive oxygen species, lipid peroxidation of –N, S donor Re(I) metal complexes - Reena R. Varma; Juhee G. Pandya; Jyoti Sharma; Chandramani Pathak; Mohan N. Patel (Molecular Diversity, 2021)

Somatic embryogenesis in Leptadenia reticulata (Retz.) Wight and Arn along with assessment of shoot and callus cultures for HPTLC fingerprint and quantification of p-coumaric acid - Swati R. Patel; Aruna G. Joshi; Ashutosh R. Pathak; Neeta Shrivastava; Sonal Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Selection and validation of differentially expressed metabolic and immune genes in weaned Ghurrah versus crossbred piglets - A. Karthikeyan; Shalu Kumari Pathak; Amit Kumar; B. A. A Sai Kumar; Aamir Bashir; Akansha Singh; N. R. Sahoo; B. P. Mishra (Tropical Animal Health and Production, 2021)

Chemical Profiling of Tylophora indica (Burm. F.) Merrill. Shoot Cultures Established Through Leaf Explant - Swati R. Patel; Ashutosh R. Pathak; Aruna G. Joshi; Neeta Shrivastava; Sonal Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Mapping of basement structure beneath the Kohima Synclinorium, north-east India via Bouguer gravity data modelling - Ch Ravi Kumar; N Kesiezie; B Pathak; Saumen Maiti; R K Tiwari (Journal of Earth System Science, 2020)

Functional variations between Mesenchymal Stem Cells of different tissue origins: A comparative gene expression profiling - K. N. Sangeetha; Rosy Vennila; R. Secunda; S. Sakthivel; Surajit Pathak; S. Jeswanth; R. Surendran (Biotechnology Letters, 2020)

Efficacy of Indolicidin, Cecropin A (1-7)-Melittin (CAMA) and Their Combination Against Biofilm-Forming Multidrug-Resistant Enteroaggregative Escherichia coli - Jess Vergis; S. V. S. Malik; Richa Pathak; Manesh Kumar; R. Sunitha; S. B. Barbuddhe; Deepak B. Rawool (Probiotics and Antimicrobial Proteins, 2020)

Determination of Morphological and Biochemical Basis of Resistance Against Top Borer, Scirpophaga excerptalis Walker in Sugarcane - S. N. Sushil; Amaresh Chandra; Sharmila Roy; A. K. Jaiswal; M. R. Singh; A. D. Pathak (Sugar Tech, 2020)

The complete mitochondrial genome of Indian featherback Chitala chitala (Osteoglossiformes) and phylogenetic status - Rajeev K. Singh; Nimisha Dutta; Abhinav Pathak; Vindhya Mohindra; Gurjeet Kaur; Rajesh Kumar; R. S. Sah; J. K. Jena; Kuldeep K. Lal (Conservation Genetics Resources, 2019)

The incretin enhancer, sitagliptin, exacerbates expression of hepatic inflammatory markers in rats fed a high-cholesterol diet - Rashmi Pathak; Avinash Kumar; Henry A. Palfrey; Laura A. Forney; Kirsten P. Stone; Narayan R. Raju; Thomas W. Gettys; Subramanyam N. Murthy (Inflammation Research, 2019)

Interplay of phosphorus doses, cyanobacterial inoculation, and elevated carbon dioxide on yield and phosphorus dynamics in cowpea - Sumit Kumar Dey; B. Chakrabarti; T. J. Purakayastha; Radha Prasanna; R. Mittal; S. D. Singh; H. Pathak (Environmental Monitoring and Assessment, 2019)

Assessment of cell-free levels of iron and copper in patients with Friedreich’s ataxia - Deepti Pathak; Achal Kumar Srivastava; Sheffali Gulati; Moganty R. Rajeswari (BioMetals, 2019)

Impact of seasonal thermal stress on physiological and blood biochemical parameters in pigs under different dietary energy levels - P. K. Pathak; R. Roychoudhury; J. Saharia; M. C. Borah; D. J. Dutta; R. Bhuyan; D. Kalita (Tropical Animal Health and Production, 2018)

RNA Seq analysis for transcriptome profiling in response to classical swine fever vaccination in indigenous and crossbred pigs - Shalu Kumari Pathak; Amit Kumar; G. Bhuwana; Vaishali Sah; Vikramadiya Upmanyu; A. K. Tiwari; A. P. Sahoo; A. R. Sahoo; Sajjad A. Wani; Manjit Panigrahi; N. R. Sahoo; Ravi Kumar (Functional & Integrative Genomics, 2017)

Weed and Nitrogen Management Effects on Weed Infestation and Crop Productivity of Wheat–Mungbean Sequence in Conventional and Conservation Tillage Practices - C. P. Nath; T. K. Das; K. S. Rana; R. Bhattacharyya; H. Pathak; S. Paul; M. C. Meena; S. B. Singh (Agricultural Research, 2017)

Genetic diversity of Indian jujube cultivars using SCoT, ISSR, and rDNA markers - S. K. Singh; Sidhika Chhajer; Rakesh Pathak; R. K. Bhatt; Rajwant K. Kalia (Tree Genetics & Genomes, 2017)

The Vitamin E Analog Gamma-Tocotrienol (GT3) Suppresses Radiation-Induced Cytogenetic Damage - Rupak Pathak; Abdel Bachri; Sanchita P. Ghosh; Igor Koturbash; Marjan Boerma; Regina K. Binz; Jeffrey R. Sawyer; Martin Hauer-Jensen (Pharmaceutical Research, 2016)

Influence of varying nitrogen levels on lipid accumulation in Chlorella sp. - B. Kiran; K. Pathak; R. Kumar; D. Deshmukh; N. Rani (International Journal of Environmental Science and Technology, 2016)

Super-Optimal NPK Along with Foliar Iron Application Influences Bioavailability of Iron and Zinc of Wheat - Rajiv Rakshit; A. K. Patra; T. J. Purakayastha; R. D. Singh; H. Pathak; Shiva Dhar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

The Stress of Suicide: Temporal and Spatial Expression of Putative Heat Shock Protein 70 Protect the Cells from Heat Injury in Wheat (Triticum aestivum) - Ranjeet R. Kumar; Suneha Goswami; Richa Gupta; Pooja Verma; Khushboo Singh; Jyoti P. Singh; Mahesh Kumar; Sushil K. Sharma; Himanshu Pathak; Raj D. Rai (Journal of Plant Growth Regulation, 2016)

Cysteine-rich secretory protein 3 plays a role in prostate cancer cell invasion and affects expression of PSA and ANXA1 - Bhakti R. Pathak; Ananya A. Breed; Snehal Apte; Kshitish Acharya; Smita D. Mahale (Molecular and Cellular Biochemistry, 2016)

Indirect organogenesis from leaf explants of Hemidesmus indicus (L.) R. Br.: an important medicinal plant - A. R. Pathak; A. G. Joshi (Plant Biosystems, 2015)

Molecular Characterization of Commercial Varieties of Phyllanthus emblica Using RAPD and Nuclear rDNA SNPs - S. K. Singh; P. R. Meghwal; Rakesh Pathak (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Calcium triggers protein kinases-induced signal transduction for augmenting the thermotolerance of developing wheat (Triticum aestivum) grain under the heat stress - Suneha Goswami; Ranjeet R. Kumar; Sushil K. Sharma; Yugal K. Kala; Khushboo Singh; Richa Gupta; Gaurav Dhavan; Gyanendra K. Rai; Gyanendra P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2015)

Salicylic acid alleviates the heat stress-induced oxidative damage of starch biosynthesis pathway by modulating the expression of heat-stable genes and proteins in wheat (Triticum aestivum) - Ranjeet R. Kumar; Sushil K. Sharma; Suneha Goswami; Pooja Verma; Khushboo Singh; Nidhi Dixit; Himanshu Pathak; C. Viswanathan; Raj D. Rai (Acta Physiologiae Plantarum, 2015)

Juvenile myelomonocytic leukemia due to a germline CBL Y371C mutation: 35-year follow-up of a large family - Anand Pathak; Alexander Pemov; Mary L. McMaster; Ramita Dewan; Sarangan Ravichandran; Evgenia Pak; Amalia Dutra; Hyo Jung Lee; Aurelie Vogt; Xijun Zhang; Meredith Yeager; Stacie Anderson; et al. (Human Genetics, 2015)

Moisture stable heteroleptic titanium (IV) complexes derived from 8-hydroxyquinoline: synthesis, antibacterial, and antifungal studies - Blassan Samuel; K. R. Ethiraj; Madhvesh Pathak (Medicinal Chemistry Research, 2015)

Molecular Markers Assisted Identification of Intraspecific Hybrids in Ziziphus mauritiana - Sunil Kumar Singh; P. R. Meghwal; Rakesh Pathak; Ragini Gautam (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Assessment of Genetic Diversity Among Indian Jujube Varieties Based on Nuclear Ribosomal DNA and RAPD Polymorphism - S. K. Singh; P. R. Meghwal; Rakesh Pathak; R. K. Bhatt; Ragini Gautam (Agricultural Research, 2014)

Ascorbic acid at pre-anthesis modulate the thermotolerance level of wheat (Triticum aestivum) pollen under heat stress - Ranjeet R. Kumar; Suneha Goswami; Kritika A. Gadpayle; Khushboo Singh; Sushil K. Sharma; G. P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2014)

Sugar Beet: A Historical Perspective in Indian Context - A. D. Pathak; Raman Kapur; S. Solomon; Rajesh Kumar; Sangeeta Srivastava; P. R. Singh (Sugar Tech, 2014)

Ammonia Emission from Rice–Wheat Cropping System in Subtropical Soil of India - S. K. Sharma; R. C. Harit; V. Kumar; T. K. Mandal; H. Pathak (Agricultural Research, 2014)

Infections do not predict shedding in co‐infections with two helminths from a natural system - Isabella M. Cattadori; Benjamin R. Wagner; Laura A. Wodzinski; Ashutosh K. Pathak; Adam Poole; Brian Boag (Ecology, 2014)
Given the health and economic burden associated with the widespread occurrence of co‐infections in humans and agricultural animals, understanding how co‐infections contribute to host heterogeneity to infection and transmission is critical if we are to assess risk of infection based on host characteristics. Here, we examine whether host heterogeneity to infection leads to similar heterogeneity in transmission in a population of rabbits single and co‐infected with two helminths and monitored monthly for eight years. Compared to single infections, co‐infected rabbits carried higher Trichostrongylus retortaeformis intensities, shorter worms with fewer eggs in utero, and shed similar numbers of parasite eggs. In contrast, the same co‐infected rabbits harbored fewer Graphidium strigosum with longer bodies and more eggs in utero, and shed more eggs of this helminth. A positive density‐dependent relationship between fecundity and intensity was found for T. retortaeformis but not G. strigosum in co‐infected rabbits. Juvenile rabbits contributed to most of the infection and shedding of T. retortaeformis , while adult hosts were more important for G. strigosum dynamics of infection and transmission, and this pattern was consistent in single and co‐infected individuals. This host–parasite system suggests that we cannot predict the pattern of parasite shedding during co‐infections based on intensity of infection alone. We suggest that a mismatching between susceptibility and infectiousness should be expected in helminth co‐infections and should not be overlooked.

Association studies of dormancy and cooking quality traits in direct-seeded indica rice - SUNAYANA RATHI; K. PATHAK; R. N. S. YADAV; B. KUMAR; R. N. SARMA (Journal of Genetics, 2014)

Trends and fluctuations of rainfall regime in the Brahmaputra and Barak basins of Assam, India - R. L. Deka; C. Mahanta; H. Pathak; K. K. Nath; S. Das (Theoretical and Applied Climatology, 2013)

Elementary empirical model to assess seismic soil liquefaction - Snehal R. Pathak; Asita N. Dalvi (Natural Hazards, 2013)

ASTER Data Analysis for Mineral Potential Mapping Around Sawar-Malpura Area, Central Rajasthan - B. K. Bhadra; Suparn Pathak; G. Karunakar; J. R. Sharma (Journal of the Indian Society of Remote Sensing, 2013)

Class Separability Analysis and Classifier Comparison using Quad-polarization Radar Imagery - Manoj Joseph; S. Rama Subramoniam; K. S. Srinivasan; Suparn Pathak; J. R. Sharma (Journal of the Indian Society of Remote Sensing, 2013)

Differential expression of heat shock protein and alteration in osmolyte accumulation under heat stress in wheat - Ranjeet R. Kumar; Suneha Goswami; Sushil K. Sharma; Khushboo Singh; Kritika A. Gadpayle; S. D. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2013)

Ammonia emission from subtropical crop land area in India - A. Datta; S. K. Sharma; R. C. Harit; V. Kumar; T. K. Mandal; H. Pathak (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Freshwater fish biodiversity in the River Ganga (India): changing pattern, threats and conservation perspectives - U. K. Sarkar; A. K. Pathak; R. K. Sinha; K. Sivakumar; A. K. Pandian; A. Pandey; V. K. Dubey; W. S. Lakra (Reviews in Fish Biology and Fisheries, 2012)

Studies on urban drinking water quality in a tropical zone - Mohana Krishna Reddy Mudiam; S. P. Pathak; K. Gopal; R. C. Murthy (Environmental Monitoring and Assessment, 2012)

Assessment of Genetic Diversity in Trigonella foenum-graecum Based on Nuclear Ribosomal DNA, Internal Transcribed Spacer and RAPD Analysis - R. K. Kakani; S. K. Singh; Anjly Pancholy; R. S. Meena; Rakesh Pathak; Aparna Raturi (Plant Molecular Biology Reporter, 2011)

Effect of Zinc Supplementation on the Status of Thyroid Hormones and Na, K, and Ca Levels in Blood Following Ethanol Feeding - R. Pathak; D. Dhawan; A. Pathak (Biological Trace Element Research, 2011)

Genomic mapping and testing for quantitative trait loci in tea (Camellia sinensis (L.) O. Kuntze) - S. M. Kamunya; F. N. Wachira; R. S. Pathak; R. Korir; V. Sharma; R. Kumar; P. Bhardwaj; R. Chalo; P. S. Ahuja; R. K. Sharma (Tree Genetics & Genomes, 2010)

Isolation and characterization of Indian isolates of camel pox virus - V. Bhanuprakash; V. Balamurugan; M. Hosamani; G. Venkatesan; Bina Chauhan; V. A. Srinivasan; R. S. Chauhan; K. M. L. Pathak; Raj Kumar Singh (Tropical Animal Health and Production, 2010)

Diagnosis of gastrointestinal tuberculosis: Using cytomorphological, microbiological, immunological and molecular techniques — A study from Central India - Pradyumna Kumar Mishra; A. Bhargava; R. P. Punde; N. Pathak; P. Desikan; A. Jain; S. Varshney; K. K. Maudar (Indian Journal of Clinical Biochemistry, 2010)

Integrated resource-driven pig production systems in a mountainous area of Northeast India: production practices and pig performance - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Anubrata Das; R. K. Bardoloi (Tropical Animal Health and Production, 2009)

Novel blue light‐sensitive proteins from a metagenomic approach - G. P. Pathak; A. Ehrenreich; A. Losi; W. R. Streit; W. Gärtner (Environmental Microbiology, 2009)
Summary A microarray‐based approach was used to screen a soil metagenome for the presence of blue light (BL) photoreceptor‐encoding genes. The microarray carried 149 different 54‐mer oligonucleotides, derived from consensus sequences of light, oxygen and voltage (LOV) domain BL photoreceptor genes. Calibration of the microarrays allowed the detection of minimally 50 ng of genomic DNA against a background of 2–5 μg of genomic DNA. Identification of a positive cosmid clone was still possible for an amount of 0.25 ng against a background of 10 μg of labelled DNA clones. The array could readily identify targets carrying 4% sequence mismatch. Using the LOV microarray, up to 1200 library clones in concentrations of c . 20 ng each with a c . 40 kb insert size could be screened in a single batch. After calibration and reliability controls, the microarray was probed with cosmid‐cloned DNA from the thermophilic fraction of a soil sample. From this approach, a novel gene was isolated that encodes a protein consisting of several Per‐Arnt‐Sim domains, a LOV domain associated to a histidine kinase and a response regulator domain. The novel gene showed highest similarity to a known sequence from Kineococcus radiotolerans SRS30216 (58% identity for the LOV domain only) and to a gene from Methylibium petroleiphilum PM1 (57% identity). The gene, designated as ht‐met1 (Hamburg Thermophile Metagenome 1), was isolated and fully sequenced (3615 bp). ht‐met1 is followed by a second open reading frame encoding a Fe‐chelatase, an arrangement quite frequent for BL photoreceptors. The LOV domain region of ht‐met1 was subcloned and expressed yielding a fully functional, flavin‐containing LOV domain. Irradiation generated the typical LOV photochemistry, with the transient formation of a flavin‐protein photoadduct. The dark recovery lifetime was found as τ REC = 120 s (20°C) and is among the fastest ones determined so far for bacterial LOV domains.

Quantitative evaluation of climatic variability and risks for wheat yield in India - H. Pathak; R. Wassmann (Climatic Change, 2009)

Reproductive pathways of seed development in apomictic guinea grass (Panicum maximum Jacq.) reveal uncoupling of apomixis components - P. Kaushal; D. R. Malaviya; A. K. Roy; Shalini Pathak; A. Agrawal; Ambica Khare; S. A. Siddiqui (Euphytica, 2008)

Stochastic Modeling of Progressive Failure in Heterogeneous Soil Slope - D. R. Pathak; H. N. Gharti; A. B. Singh; A. Hiratsuka (Geotechnical and Geological Engineering, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular cloning, expression, and cytokinin (6-benzylaminopurine) antagonist activity of peanut (Arachis hypogaea) lectin SL-I - Monika Pathak; Bharat Singh; Amit Sharma; Praveen Agrawal; Santosh B. Pasha; Hasi R. Das; Rakha H. Das (Plant Molecular Biology, 2006)

Impact of Post-Methanation Distillery Effluent Irrigation on Groundwater Quality - N. Jain; A. Bhatia; R. Kaushik; Sanjeev Kumar; H. C. Joshi; H. Pathak (Environmental Monitoring and Assessment, 2005)

Use of Flyash and Biogas Slurry for Improving Wheat Yield and Physical Properties of Soil - R. N. Garg; H. Pathak; D. K. Das; R. K. Tomar (Environmental Monitoring and Assessment, 2005)

Habitat evaluation for sarus crane in the Keoladeo National Park using IRS LISS III and pan merged data and GIS - Sarvesh Palria; Akanksha Singh; J. R. Sharma; Suparn Pathak (Journal of the Indian Society of Remote Sensing, 2005)

Soil Properties and Crop Productivity as Influenced by Flyash Incorporation in Soil - Naveen Kalra; M. C. Jain; H. C. Joshi; R. Chaudhary; Sushil Kumar; H. Pathak; S. K. Sharma; Vinod Kumar; Ravindra Kumar; R. C. Harit; S. A. Khan; M. Z. Hussain (Environmental Monitoring and Assessment, 2003)

Modelling the quantitative evaluation of soil nutrient supply, nutrient use efficiency, and fertilizer requirements of wheat in India - H. Pathak; P.K. Aggarwal; R. Roetter; N. Kalra; S.K. Bandyopadhaya; S. Prasad; H. Van Keulen (Nutrient Cycling in Agroecosystems, 2003)

Dual effect of first full term pregnancy on breast cancer risk: empirical evidence and postulated underlying biology - Dorothy R. Pathak (Cancer Causes & Control, 2002)

Effect of Testosterone Suppression on the Pharmacokinetics of a Potent GnRH Receptor Antagonist - Eugenia A. Iatsimirskaia; Margaret L. Gregory; Kenna L. Anderes; Rosemary Castillo; K. Eric Milgram; David R. Luthin; Ved P. Pathak; Lance C. Christie; Haresh Vazir; Mark B. Anderson; John M. May (Pharmaceutical Research, 2002)

Long-term changes in yield and soil fertility in a twenty-year rice-wheat experiment in Nepal - Gami S.; Ladha J.; Pathak H.; Shah M.; Pasuquin E.; Pandey S.; Hobbs P.; Joshy D.; Mishra R. (Biology and Fertility of Soils, 2001)

Soil Amendment with Distillery Effluent for Wheat and Rice Cultivation - H. Pathak; H. C. Joshi; A. Chaudhary; R. Chaudhary; N. Kalra; M. K. Dwiwedi (Water, Air, & Soil Pollution, 1999)

Withania somnifera (Ashwagandha): Regeneration through Meristem Culture - Nilesh P. Teli; Nilima M. Patil; Hema M. Pathak; Sanjeevani R. Bhalsing; Vijay L. Maheshwari (Journal of Plant Biochemistry and Biotechnology, 1999)

Health Status Utility Assessment by Standard Gamble: A Comparison of the Probability Equivalence and the Lottery Equivalence Approaches - Anandi V. Law; Dev S. Pathak; Mark R. McCord (Pharmaceutical Research, 1998)

The Imperata grasslands of tropical Asia: area, distribution, and typology - D. P. Garrity; M. Soekardi; M. van Noordwijk; R. de la Cruz; P. S. Pathak; H. P. M. Gunasena; N. van So; G. Huijun; N. M. Majid (Agroforestry Systems, 1996)

Productivity of annual cropping and agroforestry systems on a shallow Alfisol in semi-arid India - M. R. Rao; C. K. Ong; P. Pathak; M. M. Sharma (Agroforestry Systems, 1991)